THE ROLE OF THE SALATIGA CITY REGIONAL FINANCIAL AND REVENUE MANAGEMENT AGENCY IN DETERMINING MARKET VALUE FOR BPHTB TAX COLLECTION - Gondomono, Auddy Rogmanialdy; Sudarwanto, Sentot (ANAYASA : Journal of Legal Studies, 2025)
This research aims to analyze the authority of the Regional Financial and Revenue Management Agency (BPKPD), implementation, and legal consequences in determining the value of land sale and purchase transactions as a basis for determining Land and Building Rights Acquisition Fees (BPHTB) in Salatiga City. This research uses empirical normative legal research methods with statutory, conceptual and sociological approaches. The authority of the BPKPD in determining the selling price of land as a basis for determining BPHTB in the City of Salatiga is regulated in Salatiga Mayor Regulation Number 33 of 2024 concerning Guidelines for Implementing Rural and Urban Land and Building Tax Collection. In determining the BPHTB, the Salatiga City BPKPD makes adjustments to the Land and Building Tax Payable Tax Notification Letter (SPPT PBB) for the year when the BPHTB Regional Tax Payment Letter (SSPD) is reported with the determination of the amount of the PBB Tax Object Sales Value (NJOP) which has been adjusted based on the Decree of the Mayor of Salatiga for each year’s period. The factors that influence the determination of land sale and purchase prices as a basis for determining BPHTB are the data base and human resources.